Cyclotron: A Secure, Isolated, Virtual Cycle-Scavenging Grid in the Enterprise - Kane, Kevin; Dillaway, Blair (Concurrency and Computation: Practice and Experience, 2009)
Cycle-scavenging grids appeal to organizations with large numbers of workstations that remain idle outside of normal working hours. This represents a potential source of grid computing cycles, but the security and isolation issues that come with the use of non-dedicated resources have slowed their adoption in the enterprise. In this paper we present Cyclotron, a prototype cycle-scavenging grid solution that leverages virtualization and a declarative security policy-based access control infrastructure, supporting flexible authorization rules and the constrained delegation of access rights, to address these requirements. This is an extended journal version of an earlier workshop paper.